Decentralized Infrastructure and Yield-Bearing Stablecoins for Financial Inclusion - Utkarsh Sinha (International Journal of Computational and Experimental Science and Engineering, 2026)
Old economy banking infrastructure systematically bars billions of people across the globe from fundamental financial services by way of insurmountable documentation barriers, exorbitant fee systems, and geographic reach that disproportionately affect developing economy populations. Local currency instability and hyperinflation further enhance these problems by decimating savings and buying capacity, locking communities in vicious cycles of economic instability. Blockchain and decentralized financial protocols appear as revolutionary solutions that democratize access to finance using only internet connectivity, removing intermediaries and institutional gatekeeping systems. Dollar-pegged stablecoins bring much-needed stability to volatility in currencies without sacrificing the accessibility advantages of distributed ledger infrastructure. Decentralized lending protocols produce legitimate returns by linking borrowers and lenders via algorithmic interest rate models, which are transparently operated without central decision-making power. Self-custody wallets function as complete pseudo-bank debts supplying global attain and continuous accessibility, allowing customers to keep, transmit, and hold digital property without requiring institutional approval or extensive documentation. Clever contracts execute mechanically primarily based on predetermined conditions, disposing of human intermediaries at the same time as ensuring transparency via immutable public blockchain information. Revolutionary regulatory frameworks establish sandbox environments that facilitate controlled experimentation with blockchain-based economic services, enabling innovation even as preserving customer protection requirements. Mobile-first user experience design with support for local languages answers the specific needs of developing market populations relying solely on internet access via mobile devices. Intersecting these technological advancements makes financially independent ecosystems possible for serving previously excluded communities through yield-producing instruments and barrier-free cross-border payment capabilities.